2006
DOI: 10.1109/dac.2006.229274
|View full text |Cite
|
Sign up to set email alerts
|

Circuits for energy harvesting sensor signal processing

Abstract: The recent explosion in capability of embedded and portable electronics has not been matched by battery technology. The slow growth of battery energy density has limited device lifetime and added weight and volume. Passive energy harvesting from solar radiation, thermal sources, or mechanical vibration has potentially wide application in wearable and embedded sensors to complement batteries. The amount of energy from harvesting is typically small and highly variable, requiring circuits and architectures which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…In [3], [5] and [7] the authors have reported how such functions can be implemented using subthreshold designs. A standard FIR realization often employed in subthreshold designs is the transversal structure depicted in Fig.1.…”
Section: Filteringmentioning
confidence: 99%
“…In [3], [5] and [7] the authors have reported how such functions can be implemented using subthreshold designs. A standard FIR realization often employed in subthreshold designs is the transversal structure depicted in Fig.1.…”
Section: Filteringmentioning
confidence: 99%
“…Memory cells for AC supplies must hold state while the supply is low without requiring frequent refreshes which can degrade system performance. A three-transistor DRAM cell with non-destructive read was used along with a singleended sense circuit consisting of two transmission gates, a precharge transistor, and a tri-state buffer [1]. To ensure correct operation, the POR voltage threshold detection can be made dependent on the DRAM as shown in Figure 3.…”
Section: Power-on-reset and Memory Designmentioning
confidence: 99%
“…Off-chip power electronics increase system cost and volume and limit the effectiveness of vibration-based energy harvesting due to losses incurred when converting from AC to DC voltage (typical efficiencies are between 18%-65% [1]). Interfacing digital circuits directly to the rectified AC energy harvester output avoids the power and cost of complex power electronics.…”
Section: Introductionmentioning
confidence: 99%
“…However, some sources such as solar cells vary dramatically with a 24-hour solar cycle for outdoor applications [5]. The power profile of a solar cell is fluctuating and is different from a regular battery.…”
Section: Introductionmentioning
confidence: 99%